13CO2/12CO2 exchange fluxes in a clamp‐on leaf cuvette: disentangling artefacts and flux components. (25th June 2015) - Gong, Xiao Ying; Schäufele, Rudi; Feneis, Wolfgang; Schnyder, Hans
Abstract: Leaks and isotopic disequilibria represent potential errors and artefacts during combined measurements of gas exchange and carbon isotope discrimination (Δ). This paper presents new protocols to quantify, minimize, and correct such phenomena. We performed experiments with gradients of CO2 concentration (up to ±250  μ mol mol −1 ) and δ 13 CCO2 (34‰), between a clamp‐on leaf cuvette (LI‐6400) and surrounding air, to assess (1) leak coefficients for CO2, 12 CO2, and 13 CO2 with the empty cuvette and with intact leaves of H olcus lanatus (C3 ) or S orghum bicolor (C4 ) in the cuvette; and (2) isotopic disequilibria between net photosynthesis and dark respiration in light. Leak coefficients were virtually identical for 12 CO2 and 13 CO2, but ∼8 times higher with leaves in the cuvette. Leaks generated errors on Δ up to 6‰ for H . lanatus and 2‰ for S . bicolor in full light; isotopic disequilibria produced similar variation of Δ. Leak errors in Δ in darkness were much larger due to small biological : leak flux ratios. Leak artefacts were fully corrected with leak coefficients determined on the same leaves as Δ measurements. Analysis of isotopic disequilibria enabled partitioning of net photosynthesis and dark respiration, and indicated inhibitions of dark respiration in full light ( H . lanatus : 14%, S . bicolor : 58%). Abstract : Leaks and isotopic disequilibria represent potential errors and artifacts during combined measurements of gas exchange and carbon isotope discrimination (Δ). This paper presents new protocols to quantify, minimize, and correct such phenomena. Leak artifacts were corrected fully by using leak coefficients of CO2, 12 CO2, and 13 CO2 measured with intact leaves. Assessment of isotopic disequilibria between net photosynthesis and dark respiration rate in light enabled the partitioning of the two fluxes and estimation of Δ during (net) photosynthesis.